2020
DOI: 10.1111/evj.13330
|View full text |Cite
|
Sign up to set email alerts
|

Clinical magnetic resonance image quality of the equine foot is significantly influenced by acquisition system

Abstract: Background Investigation of image quality in clinical equine magnetic resonance (MR) imaging may optimise diagnostic value. Objectives To assess the influence of field strength and anaesthesia on image quality in MR imaging of the equine foot in a clinical context. Study design Analytical clinical study. Methods Fifteen equine foot studies (five studies per system) were randomly selected from the clinical databases of three MR imaging systems: low‐field standing (LF St), low‐field anaesthetised (LF GA) and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Nonetheless, scoring was performed by a specialist veterinary radiologist with extensive experience specifically in equine imaging, who was unaware of group assignment. The presence of artefacts was also graded utilising a subjective scoring system adapted from a previously published scoring system [3], and detailed definitions were provided for each grade. Thirdly, some other factors possibly affecting scan quality were not fully controlled or recorded, such as temperature and activity in adjacent rooms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, scoring was performed by a specialist veterinary radiologist with extensive experience specifically in equine imaging, who was unaware of group assignment. The presence of artefacts was also graded utilising a subjective scoring system adapted from a previously published scoring system [3], and detailed definitions were provided for each grade. Thirdly, some other factors possibly affecting scan quality were not fully controlled or recorded, such as temperature and activity in adjacent rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages are particularly evident when investigating lameness that affects the equine foot, where the hoof capsule limits the diagnostic value of conventional imaging modalities [2,3]. In addition, when compared to computed tomography (CT), low-field MRI systems (LFMRI) have been shown to produce higher anatomic visualisation scores of structures like the distal sesamoidean impar ligament, synovial structures, and the distal deep flexor tendon (DDFT) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Higher magnet strength has several clinically relevant advantages, including decreased scan times, increased resolution, larger field of view, availability of specialized sequences (eg, to evaluate articular cartilage), and overall improved image quality. 5,[16][17][18] These factors can translate into increased anatomic visibility, greater diagnostic ability, and higher diagnostic confidence in the findings. [18][19][20] One recent study 17 comparing low-field standing, low-field general anesthesia, and high-field general anesthesia MRI examinations of the equine foot found that image quality was better in high-field scans than in either type of low-field scan, indicating that higher field strength itself led to improved image quality rather than the use of general anesthesia.…”
Section: Designsmentioning
confidence: 99%
“…5,[16][17][18] These factors can translate into increased anatomic visibility, greater diagnostic ability, and higher diagnostic confidence in the findings. [18][19][20] One recent study 17 comparing low-field standing, low-field general anesthesia, and high-field general anesthesia MRI examinations of the equine foot found that image quality was better in high-field scans than in either type of low-field scan, indicating that higher field strength itself led to improved image quality rather than the use of general anesthesia. Other studies 18,[21][22][23][24] have shown higher detail and/or greater lesion detection in a variety of tissue types with high-field MRI than with low-field MRI in the foot, fetlock region, proximal metacarpus, and carpus.…”
Section: Designsmentioning
confidence: 99%